Diversity Of Bacteria In Breeding Water And Midgut Of Aedes Albopictus, And Determination Of Its Paratransgenic Candidates And Ovipositional Attractant - Mohd Fadzlah, Fadhlina Hazwani (2023)
Researchers have started to focus on vector management and implementation of biological control to replace the hazardous effect of excessive insecticide usage. This study was conducted to provide fundamental knowledge of bacteria diversity in breeding water and midgut of Aedes albopictus. The identification of these bacteria is important for its roles as paratransgenesis and oviposition attractant. The culture-dependent and culture-independent methods were used for the comparative assessment of bacteria from artificial containers with the presence and absence of larvae. Interestingly, the culture-dependant method showed a higher bacterial diversity in breeding water with the presence of larvae but higher operational taxonomic units (OTUs) in the absence of larvae by culture-independent method. These results highlighted the importance of a type of bacterium that is responsible for the attraction or deterrent effects towards mosquitoes. Higher microbiota diversity present in an adult mosquito’s midgut compared to larval stage concluded that both environmental and vertical inheritance are the microbiota sources in the midgut. The consistent presence of Bacillus cereus and Proteus mirabilis in breeding water and both stages of Ae. albopictus mosquito’s midgut served as potential early candidates for the paratransgenesis. The paratransgenic candidates tested for B. cereus and P. mirabilis showed that the B. cereus was beneficial and more suitable as paratransgenic candidate.